Автохтонні заповідні дендросозофіти українського поллісся (флористичний і популяційний аналіз, оцінка декоративності та фітоценокомпозиції) - Шерстюк, Марина Юріївна (НУБіП України, 2018)
Дисертація на здобуття наукового ступеня кандидата біологічних наук зі спеціальності 06.03.01 «Лісові культури та фітомеліорація». Національний університет біоресурсів і природокористування України. Київ, 2018. Охарактеризовано основні напрями становлення та розвитку наукових досліджень автохтонних дендросозофітів Українського Полісся. Для 58 видів, які репрезентують цю групу рослин, наведено результати інвентаризації та структурного флористичного аналізу. На підставі уніфікованих екошкал Я. П. Дідуха визначено екоамплітуди заповідних автохтонних дендросозофітів за 12 екочинниками. Доведено, що всі досліджувані види чітко диференціюються за поєднанням мінімальних та максимальних величин бальних показників уніфікованих модельних екошкал, за середніми величинами цих діапазонів, а також за значеннями абсолютної та відносної ширини реалізованих еконіш. Подано результати комплексного популяційного аналізу ценопопуляцій трьох репрезентативних видів рослин: Ledum palustre L., Chimaphila umbellata (L.) W. Barton та Oxycoccus palustris Pers. Для цих видів установлено показники популяційної щільності, а також характерні ознаки онтогенетичної, розмірної, віталітетної структур ценопопуляцій. На підставі оригінального алгоритму комплексної оцінки морфоінтегрованості рослин різних біоморф оцінено морфоінтегрованість рослин цих видів. Проаналізовано декоративність автохтонних дендросозофітів та за новітніми підходами, визначено їх роль у формуванні фітоценокомпозицій. Запропоновано композиції, сформовані з видів, які подібні за екологічними властивостями. Новітній ценопопуляційний принцип реалізовано в контексті конструювання трьох фітоценокомпозицій за участі Ledum palustre, Chimaphila umbellata та Oxycoccus palustris
A thesis for the degree of candidate of biological sciences in specialty 06.03.01 Forest Plantation and Phytomelioration. National University of Life and Environmental Sciences of Ukraine. Kyiv, 2018. Main tendencies of formation and progress of scientific researches of the autochthonous dendrosozophytes of the Ukrainian Polissia were described. Results of inventory, structural floristic analysis and evaluation of representation in nature reserve fund of Ukraine were given for 58 species that represent this group of plants. Specific nature of the reserved autochthonous dendrosozophytes, that stand out for Rosaceae species (32.8 %) prevalence in taxonomic structure, was shown. Shrubs (63.8 %) prevail in biomorphotype spectrum, and nanophanerophytes (75.0 %) dominate in phanerophyte group (69.0 %). According to the research results it was established that plants comprising 15 habitat types and 24 geographic features are presented among the reserved autochthonous dendrosozophytes. Most species belong to European type (43.5 %) and European geographic feature (19.0 %). Share of plant species of Eurasian, boreal and holarctic habitat types ranges between 6.9–17.2 %. European types (55.2 %) dominate by regional habitat type, share of European-Asian (20.7 %) and circumpolar (13.8 %) plants is much smaller. The species under research are more often (77.6 %) the phytocoenosis asectators. On the basis of the unified ecological scales of Y. P. Didukh ecological amplitudes of the reserved autochthonous dendrosozophytes with 12 environmental factors were identified. It was established that all plants together cover almost the whole range of ecological scale of a certain environment factor. Plant species are clearly differentiated by combination of score minimum and maximum values of the unified model ecological scales, by average values of these ranges, as well as by absolute and relative width values of the realized econiches. On the basis of values of the realized econiche width of 12 environmental factors under research we assessed adaptaion potential of plant species, as well as appearance of their stenoecic and eurybiontic properties. The results of the comprehensive population analysis of cenopopulations of three representative plant species were introduces in the thesis: Ledum palustre L., Chimaphila umbellata (L.) W. Barton and Oxycoccus palustris Pers. It was established that Chimaphila umbellatа cenopopulations are mainly surpassed by Ledum palustre and Oxycoccus palustris by the population field area. Ledum palustre cenopopulations stand out for the smallest values of population density and, on the contrary, Oxycoccus palustris are notable for the largest ones. It was shown that all three species are characterized by the wide representation of cenopopulations, which are incomplete by ontogenetic structure and belong to the «young» type, and in Chimaphila umbellatа they also belong to the «maturing» type. Statistically valid change of static metric and allometric parameters values by plant aggregations occurs in cenopopulations of all three species under research. Every morphoparameter maintains a certain variation degree, therefore a unique size structure is peculiar to every cenopopulation. On the basis of integrated assessment original algorithm of plant characteristics of various biomorps plant we evaluated plant morphointegration of these species. They were proven to make such sequence by morphointegration increase: Ledum palustre → Chimaphila umbellatа → Oxycoccus palustris. Ornamentality of the autochthonous dendrosozophytes was assessed in the thesis. Role of the autochthonous dendrosozophytes in phytocenocomposition creation was identified in the thesis with the use of up-to-date approaches. We suggested compositions, formed of species, similar in demand for soil water regime, their content of nitrogen, carbonates and salts, soil acidity and aeration, humidification variability, illumination, temperature regime, ombroregime and cryoregime, climate continentality, as well as combination of some of the indicated factors. The newest cenopopulation principle was implemented in the context of formation of three phytocenocompositions involving Ledum palustre, Chimaphila umbellata and Oxycoccus palustris
Keywords: автохтонні дендросозофіти; природно-заповідний фонд; структура дендросозофлори; екошкали; структура популяцій; декоративність; фітоценодизайн; Українське Полісся; autochthonous dendrosozophytes; nature reserve fund; dendrosozoflora structure